(untitled) (Journal of Universal Science Research, 2025)
This article deals with the semantic features of verbs of motion, which provide a deeper understanding of how movement is conceptualized and communicated in English. This study focuses on exploring the definitions, classifications, and semantic nuances of these verbs and emphasizes their practical applications in language use which can help language learners with their learning process.